PEMODELAN VARIABEL-VARIABEL PENGELUARAN RUMAH TANGGA UNTUK KONSUMSI TELUR ATAU SUSU DI KABUPATEN MAGELANG MENGGUNAKAN REGRESI TOBIT - Viliyan Indaka Ardhi; Agus Rusgiyono; Alan Prahutama (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Censored data is the data on a dependent variable of which most of the observations are worth less than or equal to zero while others have a certain value or more than zero. Tobit regression model is a statistical model that can overcome the problems in which many independent variables is zero or called data censored. In this research, modeling eggs or milk consumption in Magelang is analyzed using tobit regression. The data used in this research is secondary data derived from Susenas Data Magelang regency 2013. The concluding results of the final modeling shows that the educational level of householder, the amount of expenditure for food in a month, the number of children in the household and the householder’s profession give significant effect on household expenditures for the consumption of eggs or milk with a coefficient determination of is 60,31%. While the remaining 39,69 % is effected by other variables is not examined in this study such as the appetite of consumers and health factors. Keywords: Consumption of Eggs or Milk, Tobit Regression, Censored Data